The Significance of Modern Writers of Turkey and Their Influence on Contemporary English Novel - Bakheet Almuhamedy, Showket Ibraheem; Hammood, Najim Abdullah; Mahmood, Samer Dhahir (International Journal of English Literature and Social Sciences (IJELS), 2019)
Nazim Hikmet (1902 to 1963) and Yasar Kemal (1923 -) were regarded as significant modern writers of Turkey. They have contributed to the literary significance of Turkish poetry in the world literature. The literary contributions of these authors have revealed Turkey’s vibrant literary scene and legacy within the world literature. The works delivered by them have influenced the literary lovers and even contemporary writers of Turkey with their resemblance of literary style. The works delivered by these writers have nominated them for the noble prize. The poetry and literary contributions of these modern writers of Turkey are significant with unique writing style mixed with romantic flavor and humorous touch. The modern writers have narrated the culture and fiction of Eastern and Western heritage. The versatile writing style was enriched with fiction combined with romantic flavor with vibrant literary scene with magical realism and folklore. In this paper we are presenting the trends of modern writers of turkey influenced the narrating and writing style of contemporary writers. The writing style, culture, fiction and romantic touch of modern writers are inherited by Nazim Hikmet and Yasar Kemal. The influential factors of these writers have discussed in this paper.